Cigarette smoking and mitochondrial dysfunction in peripheral artery disease. (February 2023) - Guo, Michelle; McDermott, Mary M; Dayanidhi, Sudarshan; Leeuwenburgh, Christiaan; Wohlgemuth, Stephanie; Ferrucci, Luigi; Peterson, Charlotte A; Kosmac, Kate; Tian, Lu; Zhao, Lihui; Sufit, Robert; Ho, Karen; et al.
Background: This study evaluated the association of smoking with mitochondrial function in gastrocnemius muscle of people with peripheral artery disease (PAD). Methods: Participants were enrolled from Chicago, Illinois and consented to gastrocnemius biopsy. Mitochondrial oxidative capacity was measured in muscle with respirometry. Abundance of voltage-dependent anion channel (VDAC) (mitochondrial membrane abundance), peroxisome proliferator-activated receptor-γ coactivator (PGC-1α) (mitochondrial biogenesis), and electron transport chain complexes I–V were measured with Western blot. Results: Fourteen of 31 people with PAD (age 72.1 years, ABI 0.64) smoked cigarettes currently. Overall, there were no significant differences in mitochondrial oxidative capacity between PAD participants who currently smoked and those not currently smoking (complex I+II-mediated oxidative phosphorylation: 86.6 vs 78.3 pmolO2 /s/mg, respectively [ p = 0.39]). Among participants with PAD, those who currently smoked had a higher abundance of PGC-1α ( p < 0.01), VDAC ( p = 0.022), complex I ( p = 0.021), and complex III ( p = 0.021) proteins compared to those not currently smoking. People with PAD who currently smoked had lower oxidative capacity per VDAC unit (complex I+II-mediated oxidative phosphorylation [137.4 vs 231.8 arbitrary units, p = 0.030]) compared to people with PAD not currently smoking. Among people without PAD, there were no significant differences in any mitochondrial measures between currently smoking ( n = 5) and those not currently smoking ( n = 63). Conclusions: Among people with PAD, cigarette smoking may stimulate mitochondrial biogenesis to compensate for reduced oxidative capacity per unit of mitochondrial membrane, resulting in no difference in overall mitochondrial oxidative capacity according to current smoking status among people with PAD. However, these results were cross-sectional and a longitudinal study is needed.